Institution for the provision of amateur and sport fishing in Ukraine - Toryanyk Volodymyr; Novitskyi Roman; Bajdak Leonid; Rodinskyi Viktor (E3S Web of Conferences, 2023)
Amateur and sports fishing, as a new, promising type of tourism in Ukraine, as well as legislative and promising acts of its regulation and management were studied. The development of «green» tourism is one of the most relevant, at the present time, in Ukraine. For many developed countries of the world, the development of the recreational industry is one of the main sources of income for the state budget. Recreational fishing and fishing tourism are popular and highly profitable industries in the field of tourism and entertainment services. The most popular fishing tourism countries are Great Britain, Panama, Turkey, USA, Venezuela, Mexico, Australia, Finland, Norway. In the US, for one dollar spent in recreational fishing, the average income is about 17 dollars. The recreational industry can become such for Ukraine, which has all the prerequisites for its development. Ukraine has a unique natural resource potential for effective recreational fishing. The contribution of scientists of the Dnipropetrovsk Hydrobiological School of technologically transformed freshwater ecosystems to the study of the processes of formation and development of amateur (recreational) fishing in Ukraine is emphasized. These studies fit well into the global trends of scientific interest in the rapid growth of the popularity of “green” tourism (in particular, water activities, fishing tourism, recreational fishing).